Analysis of power losses for a nine-switch inverter in common-frequency mode application - Neerakorn Jarutus (2018)
© 2017 IEEE. Converter power loss analysis is one of the main knowledge bases to further handle and improve the performance and efficiency of the conversion systems. This paper significantly investigates the power losses in the reduced-switch innovation of the nine-switch inverter powering two common three-phase inductive loads with the potential operation of the common-frequency mode. A new contribution is based on a clearer and accurate analysis of the conduction and switching power losses for the insulated-gate bipolar transistors (IGBTs) and the antiparallel diodes in this unique circuit. Using the characteristic-curve-based technique, it is helpful in the simplified, flexible, and straightforward algorithm of mathematical model derivations. Simulation results can verify the proposed power loss analysis.